Not Just a Pathogen? Description of a Plant-Beneficial Pseudomonas syringae Strain - Passera, Alessandro; Compant, Stéphane; Casati, Paola; Maturo, Maria Giovanna; Battelli, Giovanna; Quaglino, Fabio; Antonielli, Livio; Salerno, Domenico; Brasca, Milena; Toffolatti, Silvia Laura; Mantegazza, Francesco; Delledonne, Massimo; et al. (Frontiers in Microbiology, 2019)
Plants develop in a microbe-rich environment and must interact with a plethora of microorganisms, both pathogenic and beneficial. Indeed, such is the case of Pseudomonas, and its model organisms P. fluorescens and P. syringae, a bacterial genus that has received particular attention because of its beneficial effect on plants and its pathogenic strains. The present study aims to compare plant-beneficial and pathogenic strains belonging to the P. syringae species to get new insights into the distinction between the two types of plant-microbe interactions. In assays carried out under greenhouse conditions, P. syringae pv syringae strain 260-02 was shown to promote plant-growth and to exert biocontrol of P. syringae pv tomato strain DC3000, against the Botrytis cinerea fungus and the Cymbidium Ringspot Virus. This P. syringae strain also had a distinct volatile emission profile, as well as a different plant-colonization pattern, visualized by confocal microscopy and gfp labelled strains, compared to strain DC3000. Despite the different behavior, the P. syringae strain 260-02 showed great similarity to pathogenic strains at a genomic level. However genome analyses highlighted a few differences that form the basis for the following hypotheses regarding strain 260-02. P. syringae strain 260-02: (i) possesses non-functional virulence genes, like the mangotoxin-producing operon Mbo; (ii) has different regulation pathways, suggested by the difference in the autoinducer system and the lack of a virulence activator gene; (iii) has genes encoding DNA methylases different from those found in other P. syringae strains, suggested by the presence of horizontal-gene-transfer-obtained methylases that could affect gene expression.